2017
DOI: 10.20622/jltajournal.20.0_76
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment Beliefs and Practices of English Teachers in Japanese Universities

Abstract: Any discussion about English education in Japan is invariably bound up with a discussion about assessment. All too often, such discussions have focused on entrance examinations and other high stakes summative tests. However, language testing and assessment do not take place in a vacuum, but are deeply affected by broader social and cultural contexts, as well as individual features of the school and the classroom. In particular, perhaps more than any other factor, it is the teachers who have great influence ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Similarly, the results of Elshawa et al (2017) revealed that their participants, who were Malaysian English language teachers in tertiary ESL classrooms, conceived the aim of language assessment to be the improvement of teaching and learning. Likewise, the participants in Wicking (2017), who were EFL teachers at Japanese universities, believed in language assessment as a positive force that could improve learning. Having a clear understanding of the aims of language assessment can help teachers align their assessment practices with these goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the results of Elshawa et al (2017) revealed that their participants, who were Malaysian English language teachers in tertiary ESL classrooms, conceived the aim of language assessment to be the improvement of teaching and learning. Likewise, the participants in Wicking (2017), who were EFL teachers at Japanese universities, believed in language assessment as a positive force that could improve learning. Having a clear understanding of the aims of language assessment can help teachers align their assessment practices with these goals.…”
Section: Discussionmentioning
confidence: 99%
“…A body of research on language teachers' beliefs and practices of assessment has been conducted in the tertiary/university context (e.g., Elshawa et al, 2017;Önalan & Karagül, 2018;Rasyid, 2022;Wang et al, 2020;Wicking, 2017). For instance, Wang et al (2020) limited their research to Chinese EFL teachers' beliefs and practices of writing assessment.…”
Section: Teachers' Beliefs About Language Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, I review empirical studies on CBA practices in TEFL that have been conducted since 2000. While many quantitative CBA studies have addressed the efficiency of CBA practices (Joo, 2016;Mak & Wong, 2018;Nunes, 2004;Song & August, 2002), qualitative research on the topic often seeks to explore teachers' and students' perceptions of CBA (Davison, 2004;Davison, 2007;Wicking, 2017). Three types of CBA activities are selected for review: portfolio, peer assessment, and self-assessment (Brown & Hudson, 1998;Lewkowicz & Leung, 2021)…”
Section: The Practice Of Cba In Teflmentioning
confidence: 99%
“…The findings showed that the teachers did not use a variety of assessment methods. On the contrary, in Japan, Wicking [21] examined the English teachers' beliefs and assessment practices and concluded that the teachers used a variety of assessments, including teacher-made paper-and-pencil tests as well as items from the textbooks. On the other hand, Yang [22] investigated the factors affecting English teachers' use of multiple classroom assessment practices among young language learners in Taiwanese elementary school.…”
Section: Literature Reviewmentioning
confidence: 99%